2006
DOI: 10.1049/el:20062620
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of bifunctional membrane electrode assemblies for unitised regenerative polymer electrolyte fuel cells

Abstract: Bifunctional membrane electrode assemblies have been fabricated using a screen printing technique, which demonstrate a repeatable and stable operation to cell current and voltages. This approach lends itself to a rapid, low-cost and repeatable fabrication process for bifunctional catalytic electrodes in polymer electrolyte membrane fuel cells and electrolysers.Introduction: The conversion and storage of energy with a high efficiency, especially a high specific energy, will be an important factor in future ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…However, due to slower kinetics and higher overpotential for OER at the oxygen electrode than cathodic processes concerning hydrogen evolution reaction at the hydrogen electrode, more effort has been devoted to the development and understanding of an efficient electrocatalyst for OER. [29][30][31][32][33][34] It has been reported that the platinum-based electrocatalyst is the most promising material for ORR over the entire range of pH, 21,[35][36][37][38][39][40] while it is ascribed as a poor OER electrocatalyst because the OER on the platinum surface needs a high overpotential (>300 mV). 41,42 Alternatively, metal oxides (e.g., ruthenium oxide and iridium oxide) have been extensively studied because they are highly active and stable in acidic media and have a wide anodic potential range.…”
Section: Sehkyu Parkmentioning
confidence: 99%
See 3 more Smart Citations
“…However, due to slower kinetics and higher overpotential for OER at the oxygen electrode than cathodic processes concerning hydrogen evolution reaction at the hydrogen electrode, more effort has been devoted to the development and understanding of an efficient electrocatalyst for OER. [29][30][31][32][33][34] It has been reported that the platinum-based electrocatalyst is the most promising material for ORR over the entire range of pH, 21,[35][36][37][38][39][40] while it is ascribed as a poor OER electrocatalyst because the OER on the platinum surface needs a high overpotential (>300 mV). 41,42 Alternatively, metal oxides (e.g., ruthenium oxide and iridium oxide) have been extensively studied because they are highly active and stable in acidic media and have a wide anodic potential range.…”
Section: Sehkyu Parkmentioning
confidence: 99%
“…[43][44][45] For the bifunctional oxygen electrode in RFCs, the electrocatalysts with a combination of platinum for ORR and metal oxide for OER have been proposed. 33,34,46 However, it has been pointed out that metal oxides are not thermodynamically stable under reducing conditions and conversely platinum is vulnerable to the oxidation by the oxidative species at high anodic potentials. 45,47 It is thus necessary to shed light on the subject of novel materials at the oxygen electrode which could improve electrocatalytic activity and tolerate rigorously oxidizing and reducing conditions during long-term operations in WEs and RFCs.…”
Section: Sehkyu Parkmentioning
confidence: 99%
See 2 more Smart Citations